The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fendo.2020.00627
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Rationale for Androgen Priming in Ovarian Stimulation

Abstract: Androgen priming has a biological basis for improving poor response during ovarian stimulation. While administration of exogenous androgens may have effects on early stages of follicle development, they are unlikely to affect the androgen concentrations in more mature follicles. Conversely, administration of hormones that increases the intra-follicular androgen concentration may have effects across a broader range of stage of follicle development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Several approaches have been attempted and are under development to improve AMA fertility by correcting hormonal deficits. Mixed results have been obtained using therapies that employ growth hormone, dihydroepiandrosterone (DHEA), or testosterone ( 22 , 23 ). As described above, activin receptor pathway blockade in midlife mice by administration of the activin decoy receptor ActRIIB:Fc lowers FSH to young levels, increases egg yield, prevents oocyte chromosome and spindle misalignments, and increases litter sizes ( 1 ).…”
Section: Current and Emerging Methods For Improving Ama Reproductive mentioning
confidence: 99%
“…Several approaches have been attempted and are under development to improve AMA fertility by correcting hormonal deficits. Mixed results have been obtained using therapies that employ growth hormone, dihydroepiandrosterone (DHEA), or testosterone ( 22 , 23 ). As described above, activin receptor pathway blockade in midlife mice by administration of the activin decoy receptor ActRIIB:Fc lowers FSH to young levels, increases egg yield, prevents oocyte chromosome and spindle misalignments, and increases litter sizes ( 1 ).…”
Section: Current and Emerging Methods For Improving Ama Reproductive mentioning
confidence: 99%
“…Letrozole changes the balance between the sex-steroids by inhibiting the conversion of androgens to oestrogens. Intraovarian androgens therefore rise, which is believed to increase the FSH receptors and promoting initial recruitment of follicles (Lossl et al, 2020).…”
Section: Impact Of Letrozole Co-treatment In Normal Respondersmentioning
confidence: 99%
“…It has also been demonstrated that co-treatment with letrozole increases the precursor androgens that may serve to upregulate FSH receptors. These two factors present a rationale for the use of co-treatment with letrozole in poor ovarian responders (POR) (Weil et al, 1999;Nielsen et al, 2011;Lossl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This involves an interaction between the theca and granulosa cells, known as the two-cell, two-gonadotropin model of follicle function. 15 Studies in mice have shown that the global absence of androgen receptors leads to aberrant folliculogenesis with lower numbers of antral follicles and fewer oocytes after stimulation, subfertility, and premature ovarian insufficiency. 16,17 Mice that specifically lack androgen receptors in ovarian granulosa cells have similarly affected reproduction, but their ovaries demonstrated fewer antral follicles and more pre-antral and atretic follicles compared with wildtype mice.…”
Section: Androgen Primingmentioning
confidence: 99%